Strategies in Increasing Foreign Tourist Visits to Halal Destination: Insights from Sabang, Indonesia - Sitepu, Novi Indriyani; Syahrizal, TM; Halim, Hendra; Razaqi, Halir; Zikran, Ghrina (Universitas Syiah Kuala, 2024)
Objective This research aims to determine the impact of increasing the intention to visit on the competitiveness of Aceh's leading tourist destinations and to develop strategic steps to increase foreign tourist visits to Sabang.Design/methodology The methodology used is a mixed method, with quantitative and qualitative data collected by concurrent triangulation design. The quantitative sample comprised 100 participants, while the qualitative sample consisted of seven informants, all sample and informant from foreign tourists.Results The impact of increasing the intention to visit on the competitiveness of Aceh's leading tourist destinations is based in large part on its halal image, with attitude also having a significant effect on tourists' intention to visit tourist destinations in Sabang. Halal awareness among international tourists can strengthen or weaken the relationship between halal image, attitude and tourists' intention to visit tourist destinations in the area. Efforts to increase foreign tourist visits can be made by developing strategic steps through the optimization of roles. For example, the government should conduct promotions, provide education, and ensure environmental cleanliness. Entrepreneurs should promote Sabang Island through social media and collaboration with the travel, provide cleaning the facilities, and build prayer rooms. The society needs to understand Sharia behavior and be able to communicate in English through training and education programs, and also needs to keep the environment clean.Research limitations/implications This study focuses on efforts to increase the number of foreign tourists in Sabang, Aceh's. The research can contribute to developing superior Sharia tourist destinations in Sabang in the future and consequently increase foreign exchange earnings from tourism.Novelty/Originality The novelty is the development of Sabang as a premium sharia tourism destination in Aceh. Unique efforts were made by increasing halal awareness and approach optimalization role uses foreign tourists perceptions. Contributions from local governments, entrepreneurs and the community are needed to increase interest in repeat visits by foreign tourists.